(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
Digital systems have grown in complexity and the clock speed increases progressively and subsequently some problems such as the latency, the throughput system and power consumption. Because of this, there is a current interest in the design of asynchronous circuits, which do not exhibit such problems. This paper show the results of asynchronous hardware implementation of the transform functions of cryptographic algorithm Threefish in its encryption process, in order to utilize the benefits of asynchronous designs in cryptography . For the specification, synthesis and simulation of asynchronous Threefish modules, an EDA (Electronic Design Automation) freeware tool called Balsa was used. Balsa defines its own hardware description language, while the implementation was using reconfigurable hardware via the ISE Design Suite Xilinx platform Inc.